SURGICAL FEATURES OF POLYTRAUMA (Novateur Publications, 2025)
The monograph Surgery of Polytrauma provides a comprehensive analysis of modern surgical approaches to managing patients with multiple traumatic injuries. Polytrauma remains one of the most complex and critical challenges in emergency and trauma surgery, requiring rapid diagnosis, multidisciplinary coordination, and timely intervention. This work explores the pathophysiological basis of polytrauma, classification systems, and current protocols for primary and secondary surgical management. Special emphasis is placed on damage control surgery (DCS), including its indications, phases, and integration with intensive care. The monograph also examines the role of modern diagnostic tools such as whole-body CT and focused assessment with sonography for trauma (FAST) in the triage and stabilization of polytrauma patients. Surgical strategies for managing injuries to the chest, abdomen, pelvis, and extremities are addressed in detail, with clinical case studies illustrating practical applications.Additionally, the monograph highlights the importance of a systematic, individualized approach to each patient, considering the severity of trauma, comorbidities, and potential complications such as sepsis or multiple organ failure. The interdisciplinary collaboration between trauma surgeons, anesthesiologists, intensivists, and rehabilitation specialists is discussed as a key element in improving survival rates and functional outcomes. This publication is intended for surgeons, emergency physicians, residents, and medical students specializing in trauma care. It may also serve as a reference for developing trauma system protocols and improving standards of care in hospitals managing severe trauma cases.